Validating a Measurement for the Ramifications of Armed Conflicts that Impact the Different Basic Needs of Human Life - Muhammad Khairi Mahyuddin; Esmail Al-Mushiki; Ismael Abujarad (2024)
This article discusses the way at validating a Measurement for the ramifications of armed conflict that impact in the different aspects of the basic needs for human life in society. the sample included (443) students and academics in three universities in Yemen, Malaysia, and Gaza Palestine. The students and academics sample chosen are from Arab the belong to countries where armed-conflict is quite dominant in during this period, The researchers followed several steps in order to validate the Measurement. These steps included (1) formulating the Measurement elements, (2) verifying the validity of the apparent consistency of the questionnaire by presenting it to the arbitrators from professors specializing in the fields of management, education and statistics and (3) using exploratory factor analysis (EFA) ) by the Statistical Package for Social Sciences (SPSS) to examine the validity Internal consistency, and analysis of correlation coefficients between variables on the Measurement, and relying on the Kaiser criterion for generating and extracting factors that exceed or equal its latent roots 1. Factor Confirmation Analysis (CFA) using the AMOS program for underlying factors that constitute a set the Measurement of this study, where the tables of standard regression weights and multiple square correlations revealed each for each item that each factor is one-dimensional. By the modelling of the structural equation (SEM) has been verified Convergence validity, differentiation validity, and compound reliability for concepts stability. The results of the study denoted that the Measurement in its final form contained (43) items distributed over six factors, according to accurate statistical treatment, and it was excluding (7) items that did not meet the standard conditions in the two programs.